If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(5x + -12) = 18 Reorder the terms: 6(-12 + 5x) = 18 (-12 * 6 + 5x * 6) = 18 (-72 + 30x) = 18 Solving -72 + 30x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '72' to each side of the equation. -72 + 72 + 30x = 18 + 72 Combine like terms: -72 + 72 = 0 0 + 30x = 18 + 72 30x = 18 + 72 Combine like terms: 18 + 72 = 90 30x = 90 Divide each side by '30'. x = 3 Simplifying x = 3
| 3g/g | | y+27=56 | | 53+2x=8x-37 | | (x^3)-(2.25x^2)=-1 | | x^3-2.25x^2=-1 | | (4*8*11)-(8*8)= | | 5x+6y-7=0 | | 2x^2-36=12 | | 3*9/22 | | 10/14*100= | | X-22=Y | | 22-5x=7x+10 | | (x^2+1)*2.25=x^2+1+2.25 | | 6y-4y=-8+2 | | 6b-5a=4 | | f(x)=-3x^2+2x+4 | | 7p+2q=-5 | | 4xln(x)=0 | | 2t+11=34 | | 4s=29 | | x^3-2.25x^2=-3.25 | | 252-9n=170 | | 20-120/7 | | -33=3x+-6 | | 2y+4x=11yequal | | 252-9n=168 | | 13x-5=4x-9 | | n*1.5*6=28-n*0.5*6 | | 3n+9n=28 | | ax-3x=4 | | N=28-3 | | -v+5+6v=1+5v+3 |